The crime of ethnic cleansing under international criminal law - Nazar, Wasan; Ibraheem, Nibras (Journal of Legal Sciences, 2022)
Ethnic cleansing is the systematic forcible removal of ethnic and religious groups from a specific area, with the intent of making the area ethnically homogeneous. Direct deportation is accompanied by genocide, rape, and destruction of property, so the crime of ethnic cleansing can be considered a crime against humanity and can be included in the Genocide Convention. Ethnic extremism is a concept linked to the use of violence and weapons by a strong party against a weaker party. Extremism and fanaticism are often behind such a crime with the aim of obliterating or concealing the oppressed group in a particular geographical area.